Improving Students English Speaking Skill Through Simulation Method At The Seventh Grade Students Of SMPN 3 WERU - Nirwana; H.Andi Achmad Dahlan; Dewi Sartika (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
One of the main goals of learning English is to improve English conversation skills. However, English conversation skills are still considered as one of the difficult skills for students. Many students face several difficulties when they want to communicate in English, even though they have studied English for years. Some of the difficulties that are often faced and complained by students include: first, they are unable to communicate in English, because they do not master English vocabulary. Second, they are afraid and lack confidence in their ability to pronounce English vocabulary and third, there is no interesting media and learning methods to involve students in communicating in English. Therefore, an effective and efficient solution is needed to increase students' interest in understanding English subjects, namely by providing interesting teaching media and effective learning methods. One of the interesting teaching media is a simulation in the form of games that contain English vocabulary that is arranged as attractively as possible